Repeated major inland retreat of Thwaites and Pine Island glaciers (West Antarctica) during the Pliocene - Keiji Horikawa; Yoshihiro Asahara; Ki-Cheol Shin; Masahiro Noda; Miyu Fujimoto; Karsten Gohl; Julia S. Wellner; Adam Klaus; Denise Kulhanek; Thorsten Bauersachs; Steven M. Bohaty; Margot Courtillat; et al. (Proceedings of the National Academy of Sciences, 2026)
The stability of the West Antarctic Ice Sheet (WAIS), crucial for predicting future sea-level rise, is threatened by ocean-forced melting in the Pacific sector of the Southern Ocean. While some geological records and ice-sheet models suggest WAIS retreat during past warm periods, reliable data constraining the extent of retreat are lacking. Detrital Nd, Sr, and Pb isotope data of sediments recently drilled at International Ocean Discovery Program (IODP) Site U1532 on the Amundsen Sea continental rise manifest repeated alternations in sediment provenance during glacial–interglacial cycles of the Pliocene (5.33 to 2.58 Mya), a time warmer than present. The variations reflect large fluctuations in WAIS extent on the Antarctic continent. A unique high Pb/low ε Nd signature of sediments found at the onset of glacial intervals (3.88, 3.6, and 3.33 Ma) is attributed to the supply of detritus sourced from plutonic rocks located in the West Antarctic interior. Its isotopic signature at Site U1532 indicates major inland retreat of the WAIS during the preceding interglacials. During peak interglacials, the ice margin had retreated inland, and icebergs rafted and deposited inland-sourced detritus over 500 km across the Amundsen Sea shelf. Subsequent readvance of grounded ice then “bulldozed” these inland-derived fine-grained sediments from the shelf down to the continental slope and rise, resulting in a high Pb/low ε Nd peak in the rise sediments. Our continuous Pliocene records provide conclusive evidence for at least five major inland retreat events of the WAIS, highlighting the significant vulnerability of the WAIS to ongoing warming.